Pengaruh Reward Dan Motivasi Kerja Terhadap Kinerja Pegawai Dengan Disiplin Kerja Sebagai Variabel Intervening Pada Badan Pendapatan Daerah Kota Padang - Addina Hayati Akilie; Ramdani Bayu Putra; Nila Pratiwi; Hasmaynelis Finis (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to determine and analyze the effect of Reward and Work Motivation on Work Discipline, with Work Discipline as an intervening variable at the Regional Revenue Agency of Padang City. This research uses a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this study consist of all employees in the secretariat field at the Regional Revenue Agency of Padang City. The research findings show that there is a positive and significant effect of Reward on Work Discipline, and a positive and significant effect of Work Motivation on Work Discipline. However, there is no positive and significant effect of Reward on Employee Performance, no positive and significant effect of Work Motivation on Employee Performance, and no positive and significant effect of Work Discipline on Employee Performance. Work Discipline mediates the effect of Reward on Employee Performance and mediates the effect of Work Motivation on Employee Performance.